Dietary intake and cardiovascular risk in children and adolescents after cancer treatment - Oliveira, Marcela Barros Barbosa de; Santos, Ramara Kadija Fonseca; Melo, Marcelle Wanderley de Lacerda; Barbosa, Kiriaque Barra Ferreira; Pires, Liliane Viana (O Mundo da Saúde, 2024)
New cancer treatments have increased the life expectancy of children and adolescents, however, they are associated with excess weight and consequently with cardiovascular risk. The objective of this study was to relate dietary intake, cancer remission time with anthropometric indices related to cardiovascular risk in children and adolescents after cancer treatment. A cross-sectional study was carried out with children and adolescents, both sexes, monitored by AVOSOS in the city of Aracaju/SE. The volunteers were evaluated regarding clinical and anthropometric aspects (weight, height, waist circumference [WC], body mass index and waist/height ratio) and food consumption using a 24-hour recall. Pearson or Spearman correlation tests were applied, with p<0.05 being significant. 24 individuals were evaluated (45.8% children and 54.2% adolescents), mean age of 11.6 ± 0.84 years and disease remission time of 26.2 months. The types of cancers reported were leukemia, head and neck, lymphoma and other types (33.3%, 25.0%, 25.0% and 16.7%, respectively). Excess weight/obesity, abdominal fat and increased risk for cardiovascular disease were observed in 62.5%, 41.7% and 58.3% of the sample. The majority of participants had insufficient intake of fiber (95.8%), calcium (91.7%), iron (66.7%) and potassium (100%). A positive correlation was observed between WC and calories consumed (r=0.411, p=0.046) and dietary iron (r=0.407, p=0.049). The other variables analyzed were not correlated. Children and adolescents who survive cancer have an increased cardiovascular risk and a positive correlation between WC and caloric intake and dietary iron.